Identifikasi Penyebab Terjadinya Landing Gear Indication Tidak Berfungsi Normal pada Pesawat Boeing 737-900 ER - Mohamad Alif Dzulfiqar; Nabila Ayu Saputri; Nova, Muhammad Andi; James Siregar; Lalu Giat Juangsa Putra; Nur Rafia Dija; Meilani Mandhalena (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
The Boeing 737-900 ER aircraft has a system called landing gear indication which in its application uses a proximity sensor that is useful in providing information about the position of the landing gear. However, this system can experience problems where if the landing gear indication does not function, the pilot cannot obtain information from the instrument that ensures the position of the landing gear. The purpose of this study is to identify problems that often occur in the landing gear indication system on the aircraft. The analysis was carried out using the Root Cause Analysis (RCA) method with the Fishbone Diagram approach. From the identification results, it was found that the main cause was a problem with the proximity switch sensor experiencing corrosion and changes in position which caused the signal reading to be inaccurate. For this reason, it is necessary to replace components and adjust the sensor position so that the system can run properly.